Meteorological data from ice-free areas in Yukidori Zawa, Langhovde and Kizahashi Hama, Skarvsnes on Sôya Coast, East Antarctica during December 2014-December 2016 (National Institute of Polar Research, 2019)
Meteorological data recorded by automatic weather stations (AWSs) installed at ice-freeareas in the middle of Yukidori Zawa and near the coast of Kizahashi Hama during the JARE-56–58 (2014–2016) was summarized in tables and figures. Almost two-year data of air temperature, relative humidity, air pressure, wind conditions, solar radiations including photosynthetically active radiation and ultraviolet radiation were compiled in 3 text files from each AWS:10-min; 1-hr and daily.